Thirteen-band Tight-binding Model for the MoS2 Monolayer - Luiz Antonio Meneghetti Junior; Alexys Bruno-Alfonso (Materials Research, 2021)
A tight-binding model is fitted to density-functional calculations of the electronic structure of the MoS2 monolayer. The model involves 13 atomic orbitals per unit cell: the 4d orbitals of the molybdenum atom plus the 3s and 3p orbitals of each sulfur atom. The hopping and overlap couplings of each atom with its first nearest neighbors in each crystalline sublattice are considered. Different values are allowed for the intraplane and interplane S-S hopping integrals. A closed-form expression is given for the effective-mass tensor at stationary points. The isotropy of the valence and conduction bands near the edges of the fundamental gap is proven. The role played by the orbital overlapping as well as the crystal-field splitting of the molybdenum 4d level is discussed.